Relatório do estágio curricular supervisionado em medicina veterinária área de concentração: clínica médica de pequenos animais - (:unkn) unknown (Universidade Federal do Pampa, 2023)
The present report aims to describe the activities observed and carried out by the intern during the supervised internship in veterinary medicine, held at Vet Dor’t Hospital, in the city of Cabo Frio, Rio de Janeiro, in small animal medical clinic, under the guidance of Prof. Dr. Paulo de Souza Junior and the supervision of the veterinarian Munique Prata. The internship lasted from August 7th to October 27th, 2023, totaling 490 hours. Among the activities observed, clinical appointments, performance of complementary imaging examinations, chemotherapy, and ambulatory procedures can be mentioned. In addition to the clinical routine, other areas of veterinary medicine were observed, such as the surgical clinic, intensive care, and the hospital's clinical analysis laboratory. Among the activities the intern had more freedom to perform, venipuncture, catheterization, parameter measurement, and medication administration were highlighted. Clinical appointments and the routine of hospitalization were the most observed activities during this period. Regarding clinical appointments, 95 consultations were observed, 77 of which were new cases and 18 were follow-ups, with the canine species being the most prevalent, with 76 dogs and 17 cats treated. For the discussion, two cases of relevance to clinical medicine were chosen: heartworm disease in a canine and cutaneous haemangiosarcoma, and in a canine patient. Completing supervised veterinary medical internship was a significant personal and professional learning experience, providing practical knowledge in addition to the theoretical teachings of the undergraduate program, as well as offering exposure to a veterinary hospital, assisting in the development of ethical and professional character.
Report of the supervised curricular internship in veterinary medicine concentration area: small animal medical clinic
Keywords: Dirofilaria immits; Lakes region; Cutaneous haemangiossarcoma; Chemotherapy; Veterinary hospital; Dirofilaria immits; Região dos lagos; Hemangiossarcoma cutâneo; Quimioterapia; Hospital veterinário; CNPQ::CIENCIAS AGRARIAS